FROM PROTEST TO PURCHASE: BOYCOTT CAMPAIGNS IMPACT ON LOCAL COFFEE BRAND CONSUMPTION AND RE-CONSUMPTION IN MALAYSIA - Ismalaili Ismail; Sabiroh Md Sabri; Ismaanzira Ismail; Nursyamilah Annuar (Journal of Islamic, Social, Economics and Development, 2024)
The consumption of both international and local coffee brands has become increasingly popular in Malaysia, particularly among adolescents and the millennial generation. Consequently, coffee consumption in Malaysia has grown and flourished in line with consumer needs and demands. The various factors influencing consumers towards coffee consumption are significant and a major concern in marketing and behavioural studies. Factors such as price and perceived quality have been identified as key influencers in the consumption and re-consumption of local coffee brands in Malaysia. However, recent boycott campaigns against US-produced products are hypothesized to impact the relationship between these factors and the re-consumption of local coffee brands in Malaysia. This study aims to measure the effect of boycott campaign in moderating the relationship between price, perceived quality and re-consumption of local coffee brands among Malaysian university students. A survey of 234 respondents was conducted using non-probability sampling, involving university students across Malaysia. The results reveal that boycott campaigns do not significantly alter the impact of price or perceived quality on the re-consumption of local coffee brands. In other words, the relationships between price and re-consumption, and between perceived quality and re-consumption, remain consistent regardless of the presence of a boycott campaign. Based on these findings, it is recommended that owners of local coffee brands focus on maintaining competitive pricing and consistently high perceived quality, as these factors are crucial for driving re-consumption regardless of external factors like boycott campaigns. Additionally, enhancing quality assurance, implementing loyalty programs, and engaging with consumers through targeted marketing campaigns can further strengthen their market position and foster customer loyalty. Furthermore, understanding these dynamics provides a competitive advantage, as consumer trends and behaviours constantly evolve with different generations and environmental settings.